Grievance Redress Mechanisms in the Public Sector: A Literature Review - Pande, Suchi; Hossain, Naomi (Open Government Partnership and Accountability Research Center, 2022)
Grievance redress mechanisms (GRMs) in the public sector are institutionalized processes designed to enable people to complain about and seek redress for services they rightfully should have received. This paper reviews evidence on GRMs from around the world, focusing on mechanisms attached to public services and programs in the Global South, where they are relatively new and emerging fast. GRMs matter in particular in the Global South because they are increasingly widespread and found in multilateral aid programs, across national governments, within specific programs and services, as well as in the private sector. GRMs are expected to improve public service efficiency, effectiveness, and fairness by giving people a systematic means of seeking redress for governance failures, and they have strong potential to improve accountability to the most excluded and marginalized people, who tend to find it most difficult to make claims on their state. The review includes a simple framework for understanding the key elements of successful GRMs, as identified through the review process. These are: • Citizen capacity to complain • State capacity to respond • Proactive transparency The review concludes with key research questions to improve our understanding of how GRMs work and could be better designed and implemented.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; governance / governação; mecanismos de reclamação / grievance redress mechanisms; ⛔ No DOI found

The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

How Do Donor-led Empowerment and Accountability Activities Take Scale into Account? Evidence from DFID Programmes in Contexts of Fragility, Conflict and Violence - Anderson, Colin; Fox, Jonathan; Gaventa, John (2020)
Development donors invest significantly in governance reform, including in contexts characterised by conflict and fragility. However, there is relatively little comparative study of their change strategies, and little understanding of what works and why. This paper explores the strategies of six recent DFID-funded programmes in Mozambique, Myanmar, and Pakistan with empowerment and accountability aims. Document review and field interviews are used to analyse the application of multi-scalar or multi-level change strategies, since such approaches are hypothesised to potentially generate more leverage for public accountability reforms. Analysis suggests that these strategies can strengthen citizen ability to navigate governance systems to resolve problems and claim accountability, and can bolster pro-accountability coalitions’ internal solidarity and external legitimacy. Multi-level strategies also appear associated with establishing more significant pressure for reform than exclusively local or national approaches. Yet conventional project reporting focuses on counting activities and outputs rather than analysing the dynamic, interactive processes at work in these strategies, and few evaluations are publicly accessible. To fully understand what kinds of action strengthen citizen demands for accountability requires a more transparent and rigorous approach to learning from donor-led governance interventions.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The implementation of ASEAN single window in Indonesia as an effort to facilitate the flow of import and export in Indonesia - Arifin, Jamilah (2020)
On 9 December 2005, All ASEAN member countries signed the Agreement to Establish and Implement the ASEAN Single Window. ASEAN Single Window (ASW) is a one window system that connects ASEAN countries or National Single Window (NSW) to facilitate the electronic exchange of customs data that can be used by traders to obtain permits, customs clearance, and other documents. Indonesia has been implementing this Agreement from 2008 with the system of Indonesia National Single Window (INSW) in order to improve the smooth flow of goods and the performance of export-import services. By using the normative legal research, the research aims to determine the implementation of the ASEAN Single Window (ASW) system as an effort to facilitate the flow of exports and imports in Indonesia. The research shows that the implementation of ASEAN Single Window in Indonesia through Indonesia National Single Window System has helped improve efficiency and import export activities through its service contribution.
Keywords: *indexed; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

One-stop service policy as a bureaucratic reform in Indonesia - Umar, Akmal; Madani, Muhlis; Amrin; Farida, Umi; Yusriadi, Yusriadi; Elpisah; Bin Tahir, Saidna; Sakkir, Geminastiti (Academy of Strategic Management Journal, 2019)
Bureaucratic reform is an effort to improve the system of government administration, especially institutional aspects, management, and human resources of the apparatus. One of the bureaucratic reforms in Indonesia is the establishment of the One-Stop Service (OSS) office which handles and integrates all forms of licensing. This article examined how the implementation of public service reform and how the change of management practices had been implemented in the OSS of Bone Regency. Data were collected through a semi-structured interview with 16 of OSS' employees and nine service-users. This study applied a qualitative approach using a case study design. Techniques of data collection used three kinds of
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Citizen engagement in public services in low- and middle-income countries: A mixed-methods systematic review of participation, inclusion, transparency and accountability (PITA) initiatives - Waddington, Hugh; Sonnenfeld, Ada; Finetti, Juliette; Gaarder, Marie; John, Denny; Stevenson, Jennifer (Campbell Systematic Reviews, 2019)
Background How do governance interventions that engage citizens in public service delivery planning, management and oversight impact the quality of and access to services and citizens’ quality of life? This systematic review examined high quality evidence from 35 citizen engagement programmes in low- and middle-income countries that promote the engagement of citizens in service delivery through four routes: participation (participatory priority setting); inclusion of marginalised groups; transparency (information on rights and public service performance), and/or citizen efforts to ensure public service accountability (citizen feedback and monitoring); collectively, PITA mechanisms. We collected quantitative and qualitative data from the included studies and used statistical meta-analysis and realist-informed framework synthesis to analyse the findings. Results The findings suggest that interventions promoting citizen engagement by improving direct engagement between service users and service providers, are often effective in stimulating active citizen engagement in service delivery and realising improvements in access to services and quality of service provision, particularly for services that involve direct interaction between citizens and providers. However, in the absence of complementary interventions to address bottlenecks around service provider supply chains and service use, citizen engagement interventions alone may not improve key wellbeing outcomes for target communities or state-society relations. In addition, interventions promoting citizen engagement by increasing citizen pressures on politicians to hold providers to account, are not usually able to influence service delivery. Conclusions The citizen engagement interventions studied were more likely to be successful: (1) where the programme targeted a service that citizens access directly from front-line staff, such as healthcare, as opposed to services accessed independently of service provider staff, such as roads; (2) where implementers were able to generate active support and buy-in for the intervention from both citizens and front-line public service staff and officials; and (3) where the implementation approach drew on and/or stimulated local capacity for collective action. From a research perspective, the review found few studies that investigated the impact of these interventions on women or other vulnerable groups within communities, and that rigorous impact evaluations often lack adequately transparent reporting, particularly of information on what interventions actually did and how conditions compared to those in comparison communities.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Challenges and Strategies in Place-Based Multi-Stakeholder Collaboration for Sustainability: Learning from Experiences in the Global South - Ayala-Orozco, Bárbara; Rosell, Julieta A.; Merçon, Juliana; Bueno, Isabel; Alatorre-Frenk, Gerardo; Langle-Flores, Alfonso; Lobato, Anaid (Sustainability, 2018)
Addressing complex environmental problems requires the collaboration of stakeholders with divergent perspectives, a goal that is challenged by diverse factors. Challenges hindering multi-stakeholder collaboration (MSC) for sustainability have previously been addressed in the context of transnational partnerships. However, less is known regarding how place-based MSC operates, especially in the context of the Global South. To contribute to addressing the factors that hinder place-based MSC for sustainability in the Global South, we analyzed 38 MSC projects spanning diverse ecological and social contexts across Mexico. In a series of participatory workshops, 128 stakeholders from academia, government, business, local communities, and civil society organizations discussed factors that hinder place-based MSC and co-constructed strategies to strengthen collaboration. Some challenges coincided with those identified in previous studies (e.g., divergent visions, inadequate project planning), whereas other concerns that have not been commonly regarded as important emerged as crucial obstacles for MSC. We discuss these challenges in the context of areas of limited statehood and point to the traditions of popular education and participatory action research as a source of valuable tools for place-based MSC. We identify strategies capable of addressing diverse challenges, a result that could aid prioritizing resource allocation to strengthen MSC.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; collaboration / colaboração

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues; Mersin, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The Performance of Indonesia’s Public Credit Guarantee Scheme for MSMEs: A Regional Comparative Perspective - Tambunan, Tulus T.H. (Journal of Southeast Asian Economies, 2018)
Access to finance has been a key constraint for Indonesia’s micro, small and medium enterprises (MSMEs) that lack tangible assets to be used as collateral. Consequently, credit guarantee schemes (CGSs) are important instruments to meet MSMEs’ financial needs. This paper examines the effectiveness of the KUR (community business credit), a partial public CGS in Indonesia, by comparing it with similar schemes in other ASEAN member states (AMS). The findings suggest that the KUR programme, despite its limited coverage, has been quite effective throughout the country. Some of the critical factors behind its success include: wide dissemination of the programme; simplicity of the application procedure; full participation and support from banks; and strong coordination between all stakeholders.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Analysis Banking Role to Performance Improvement on Indonesia Small Medium Enterprises - Hedwigis (EUROPEAN RESEARCH STUDIES JOURNAL, 2017)
This study aims to analyze the role of banks to increase small and medium enterprises and economic growth in Yogyakarta province, Indonesia. The focus of this study examines how the role of banks in terms of lending to small and medium enterprises, credit to the private sector and its impact on economic growth in Yogyakarta Province. The data used in this research is secondary data obtained from the Central Bureau of Statistics.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Rethinking Indonesia’s Informal Sector - Rothenberg, Alexander D.; Gaduh, Arya; Burger, Nicholas E.; Chazali, Charina; Tjandraningsih, Indrasari; Radikun, Rini; Sutera, Cole; Weilant, Sarah (World Development, 2016)
This paper reviews competing theories about the causes of informality in developing countries and uses new data to determine which theory best explains the persistence and scale of Indonesia’s informal sector. Using nationally representative survey data on micro, small, and medium-sized firms, we find that most of Indonesia’s informal firms are very small, micro firms, with less than five employees. These firms pay low wages, are relatively unproductive when compared to large firms, are managed by individuals with low educational attainment, predominantly supply products to local markets, and have not recently attempted to expand their operations. From a small-scale, qualitative survey of firms, we find that many informal firms do not register their businesses either because they have no desire to expand or borrow from formal financial sources, or because they are avoiding taxes. Finally, we evaluate the impact of Indonesia’s one-stop-shops for business registration program, a large-scale program that attempted to reduce registration costs. We find both that the program had no effects on firms’ informality rates, and we also find that it did not reduce the probability that workers were informally employed. Taken together, the evidence suggests that a combination of the rational exit and the dual economy theories best explains why so many firms in Indonesia are informal.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Social Accountability: What Does the Evidence Really Say? - Fox, Jonathan A. (World Development, 2015)
Empirical evidence of tangible impacts of social accountability initiatives is mixed. This meta-analysis reinterprets evaluations through a new lens: the distinction between tactical and strategic approaches to the promotion of citizen voice to contribute to improved public sector performance. Field experiments study bounded, tactical interventions based on optimistic assumptions about the power of information alone, both to motivate collective action and to influence the state. Enabling environments for collective action combined with bolstered state capacity to respond to citizen voice are more promising. Sandwich strategies can help ‘voice’ and ‘teeth’ to become mutually empowering, through state–society synergy.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; transparency / transparência

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

The geographic and sectoral patterns of large-scale farmland investments in sub-Saharan Africa - Schoneveld, George Christoffel (Food Policy, 2014)
Following the food and energy price crises of the mid 2000s, sub-Saharan Africa has become one of the largest recipients for large-scale farmland investments. While much has been written on the phenomenon, scant reliable empirical evidence is available as to the precise geographic and sectoral patterns and underlying drivers. Employing strict data quality requirements, this paper addresses these knowledge gaps by analyzing 563 farmland projects that have been established between 2005 and 2013 in sub-Saharan Africa. Findings show that the investment intensity and associated risks are not geographically uniform. Moreover, the study highlights a number of popular misconceptions regarding investor origin and their sectoral interests and motives.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Disrespect and Abuse During Childbirth in Tanzania: Are Women Living With HIV More Vulnerable? - Sando, David; Kendall, Tamil; Lyatuu, Goodluck; Ratcliffe, Hannah; McDonald, Kathleen; Mwanyika-Sando, Mary; Emil, Faida; Chalamilla, Guerino; Langer, Ana (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2014)
Introduction: HIV-related stigma and discrimination and disrespect and abuse during childbirth are barriers to use of essential maternal and HIV health services. Greater understanding of the relationship between HIV status and disrespect and abuse during childbirth is required to design interventions to promote women's rights and to increase uptake of and retention in health services; however, few comparative studies of women living with HIV (WLWH) and HIV-negative women exist. Methods: Mixed methods included interviews with postpartum women (n = 2000), direct observation during childbirth (n = 208), structured questionnaires (n = 50), and in-depth interviews (n = 18) with health care providers. Bivariate and multivariate regressions analyzed associations between HIV status and disrespect and abuse, whereas questionnaires and in-depth interviews provided insight into how provider attitudes and workplace culture influence practice. Results: Of the WLWH and HIV-negative women, 12.2% and 15.0% reported experiencing disrespect and abuse during childbirth (P = 0.37), respectively. In adjusted analyses, no significant differences between WLWH and HIV-negative women's experiences of different types of disrespect and abuse were identified, with the exception of WLWH having greater odds of reporting non-consented care (P = 0.03). None of the WLWH reported violations of HIV confidentiality or attributed disrespect and abuse to their HIV status. Provider interviews indicated that training and supervision focused on prevention of vertical HIV transmission had contributed to changing the institutional culture and reducing HIV-related violations. Conclusions: In general, WLWH were not more likely to report disrespect and abuse during childbirth than HIV-negative women. However, the high overall prevalence of disrespect and abuse measured indicates a serious problem. Similar institutional priority as has been given to training and supervision to reduce HIV-related discrimination during childbirth should be focused on ensuring respectful maternity care for all women.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Promoting SME development in Indonesia - Mourougane, Annabelle (OECD Economics Department Working Papers, 2012)
Micro, small and medium-sized firms (MSMEs) are a key source of employment and economic growth in Indonesia. They contributed to the country’s economic resilience during the 2008-09 financial crisis. But many suffer from low productivity, curbing their role in boosting living standards. There are several ways to spur MSME productivity growth over the medium term. The first route would be to encourage the formalisation of small firms. Lessening red tape through simplification of the licensing process and lower tax compliance costs would help. Avoiding excessive rises in the minimum wage in provinces where it is already at a reasonable level would also be important. Looking forward, it would be useful to remove rigidities in the formal labour markets, while moving to some form of unemployment benefit system to insure workers against job-loss risks. The second route would be to boost investment. Clarifying property rights for real estate, and making the information collected by the credit bureau available to all financial institutions would ease access to finance. At the same time, the development of financing alternatives such as venture capital, leasing or micro-finance would enhance credit supply. The poor state of infrastructure, in particular in the transportation and electricity sectors, is also perceived as an important impediment to investment and could be remedied by increasing public infrastructure spending on cost-effective projects. The third route would be to enhance the quality of human resources. The country suffers from a lack of skilled workers, and policies should aim both at increasing the pool of workers and making education and training institutions more responsive to evolving labour-market demand. Indonesia has a long tradition of supporting MSMEs. But responsibilities between the different levels of government and within the central government need to be clarified to minimise overlap and inefficiencies. A rigorous assessment of existing programmes would allow schemes to be consolidated and scarce public funds to be directed to their most cost-effective uses.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Decentralization and Economic Performance in Indonesia - Pepinsky, Thomas B.; Wihardja, Maria M. (Journal of East Asian Studies, 2011)
Indonesia's 1999 decentralization law gave local governments in Indonesia an unprecedented opportunity to adopt prodevelopment policies. In this article, we study whether decentralization has in fact generated improved economic performance in Indonesia. Using a synthetic case control methodology, we argue that Indonesian decentralization has had no discernable effect on the country's national-level economic performance. To explain why not, we use subnational data to probe two political economy mechanisms-interjurisdictional competition and democratic accountability-that underlie all theories linking decentralization to better economic outcomes. Our findings suggest that extreme heterogeneity in endowments, factor immobility, and the endogenous deterioration of local governance institutions can each undermine the supposed development-enhancing promises of decentralized government in emerging economies such as Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

Collaboration and competition in a children's health initiative coalition: A network analysis - Valente, Thomas W.; Coronges, Kathryn A.; Stevens, Gregory D.; Cousineau, Michael R. (Evaluation and Program Planning, 2008)
Activating communities to achieve public health change and initiate policy reform usually requires collective action from many entities. This case study analyzes inter-organizational networks among members of a coalition created to expand health insurance coverage to uninsured children in a large metropolitan area. Six networks were measured: collaboration, competition, formal agreements, receive funding from, send funding to, and greater communication. The response rate was 65.8% (50 of the 76 active members). Positive network questions such as “who do you collaborate with” elicited many network choices whereas negative ones such as “who do you compete with” elicited few. The collaboration network had a core–periphery structure and analysis showed that a large network can be reduced to a small set of core organizations one-sixth the size of the whole. Centrality (out- and in-degree) was associated with perceived organizational function and perceived barriers to success. For example, organizations that received many choices as collaboration partners were more likely to perceive the coalition functioned well than those who received few choices. The study suggests that perceptions of organizational performance are associated with position in the network, central members are more likely to perceive the organization performs well than those on the periphery.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; access to services / acesso a serviços; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Conceptualizing and Measuring Collaboration - Thomson, A. M.; Perry, J. L.; Miller, T. K. (Journal of Public Administration Research and Theory, 2007)
This article conceptualizes and measures collaboration. An empirically validated theory of collaboration, one that can inform both theory and practice, demands a systematic approach to understanding the meaning and measurement of collaboration. We present ﬁndings from a study that develops and tests the construct validity of a multidimensional model of collaboration. Data collected using a mail questionnaire sent to 1382 directors of organizations that participate in a large national service program provides the basis for a higher order conﬁrmatory factor analysis. The model that emerges from this analysis demonstrates an overall close ﬁt with the empirical data and the high, standardized gamma coefﬁcients estimated in the model conﬁrm that ﬁve key dimensions contribute to an overall construct of collaboration. The primary purpose of this research was to stimulate interest in measurement of collaboration and reﬁnement of the model. As such, we present a detailed description of the analytical process, identify areas that affect interpretation of the data (such as possible selection bias), and propose areas for future research. We believe this effort to conceptualize and measure collaboration offers a foundation for further research.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; collaboration / colaboração

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Health providers’ opinions on provider–client relations: results of a multi-country study to test Health Workers for Change - Fonn, S; Mtonga, AS; Nkoloma, HC; Bantebya Kyomuhendo, G; Dasilva, L; Kazilimani, E; Davis, S; Dia, R (Health Policy and Planning, 2001)
A multi-centre study in four African countries was undertaken to test the acceptability and effectiveness of Health Workers for Change, a methodology to explore provider–client relations within a gender-sensitive context. This intervention addresses the interpersonal component of quality of care. The methodology, consisting of six workshops, was implemented by research teams in Zambia, Senegal, Mozambique and Uganda. It was found to be acceptable within in a range of cultural and primary health care settings. The workshops allowed difficult issues such as prejudice and bribery to be discussed openly, fostered problem solving and the development of practical plans to address problems that could strengthen district health systems.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde

What Happens to the State in Conflict?: Political Analysis as a Tool for Planning Humanitarian Assistance - Cliffe, Lionel; Luckham, Robin (Disasters, 2000)
It is now part of received wisdom that humanitarian assistance in conflict and post-conflict situations may be ineffective or even counterproductive in the absence of an informed understanding of the broader political context in which so-called ‘complex political emergencies’ (CPEs) occur. Though recognising that specific cases have to be understood in their own terms, this article offers a framework for incorporating political analysis in policy design. It is based on a programme of research on a number of countries in Africa and Asia over the last four years. It argues that the starting-point should be an analysis of crises of authority within contemporary nation-states which convert conflict (a feature of all political systems) into violent conflict; of how such conflict may in turn generate more problems for, or even destroy, the state; of the deep-rooted political, institutional and developmental legacies of political violence; and of the difficulties that complicate the restoration of legitimate and effective systems of governance after the ‘termination’ of conflict. It then lists a series of questions which such an analysis would need to ask — less in order to provide a comprehensive check-list than to uncover underlying political processes and links. It is hoped these may be used not only to understand the political dynamics of emergencies, but also to identify what kinds of policy action should and should not be given priority by practitioners.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; governance / governação